2018
DOI: 10.1002/hpja.207
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in community initiatives to increase vegetable consumption

Abstract: Issue addressed Public health concerns about insufficient consumption of vegetables across all demographics in Australia have led to 20 years of behaviour change interventions ranging from social marketing to interactive small group programs, with modest results. To maximise health promotion intervention outcomes, practitioners need up‐to‐date information that helps them navigate the complexity of food systems and eating behaviours. Methods This scoping review of Australian and international research, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…The increased feeling of connection and belonging to their local community contributed to participants feeling less isolated and more supported. This attribute of community gardening is well documented by other studies . Community gardening is recognised as conferring collective efficacy whereby the benefits extend beyond the gardening experience and the garden setting to positively impact broader aspects of individual and community life .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The increased feeling of connection and belonging to their local community contributed to participants feeling less isolated and more supported. This attribute of community gardening is well documented by other studies . Community gardening is recognised as conferring collective efficacy whereby the benefits extend beyond the gardening experience and the garden setting to positively impact broader aspects of individual and community life .…”
Section: Discussionsupporting
confidence: 63%
“…Through their involvement in growing and sharing food, participants reported higher levels of household fruit and vegetable consumption. This has also been reported by Noy et al and Barnidge et al . Programs like MH can therefore be said to have contributed to improving food and nutrition security, defined as adequate access to safe, nutritious and socially acceptable food .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social engagement and positive dietary changes were also reported by Kaye Mehta and colleagues through community gardening with participants reporting the consumption of a wider variety of fruit and vegetables. A scoping review of community initiatives and interventions associated with vegetable intake identified the opportunity for community‐driven initiatives within local food systems to increase vegetable consumption and a potential to build healthy public policy. Sharleen Gonzalez and colleagues report few junior community football clubs have a written healthy eating policy or practices to increase the availability of healthier soft drinks, fruit and vegetables despite support from club representatives and parents/carers.…”
mentioning
confidence: 99%